Philippine International Labor Migration in the Past 30 Years: Trends and Prospects - Aniceto Jr. C. Orbeta; Michael Ralph M. Abrigo (Philippine Institute for Development Studies (PIDS), 2009)
The paper characterizes how international labor migration became an enduring feature in the country's development. It presents data on the flow of temporary and permanent international migrant workers in the last thirty years. Characteristics such as destination, occupation, education, sex, and age are presented. Using historical movements and motivations, the study then presented the likely prospects of the Philippine international labor migration market considering domestic and the global labor market developments. Long-term and short-term prospects were discussed and economic, demographic, political, and environmental factors were considered as factors affecting the future flow of international migrant workers.
Keywords: J61; 330; Philippines; international labor migration; Arbeitsmigranten; Philippinen